Mild Neurocognitive Disorder: An Old Wine in a New Bottle. Issue 5 (September 2015) - Stokin, Gorazd B.; Krell-Roesch, Janina; Petersen, Ronald C.; Geda, Yonas E.
Abstract : Abstract: The American Psychiatric Association has recently published the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). The DSM-IV category "Dementia, Delirium, Amnestic, and Other Cognitive Disorders" has undergone extensive revision. DSM-5 has renamed this category as "Neurocognitive Disorders" (NCD), which now covers three entities: delirium, major NCD, and mild NCD. The DSM-IV version of mild NCD resembles the DSM-5 version in name only. DSM-IV defined mild NCD based on a single criterion, whereas DSM-5 defines mild NCD by using several cognitive and related criteria. The main difference between mild NCD and the Key International Symposium criteria of mild cognitive impairment (MCI) is that the research work that led to the construct of MCI primarily involved elderly study participants (even though age was not part of the definition of MCI), whereas mild NCD includes acquired cognitive disorders of all age groups. DSM-5 essentially discusses the epidemiology and diagnostic markers of mild NCD by drawing congruence between MCI and mild NCD. The DSM-5 definition of mild NCD is anchored on four criteria and two specifiers. The four criteria refer to cognitive changes, functional activities, and exclusion of delirium and competing mental disorders. The two specifiers are the presumed etiologies of mild NCD and the presence or absence of behavioral problems. While the category "mild NCD" may improve reliability of diagnoses, it has yet to withstand scientific scrutiny to be considered a valid construct. This article reviews the DSM-5 criteria for mild NCD, compares them with the Key International Symposium MCI criteria, and discusses the pros and cons of the mild NCD construct.